The Rohingya Influx into Bangladesh’s Cox’s Bazar: Mapping Internal Security Threats - Ahmed, Saifuddin; Siddiqui, Muhammad Sazzad Hossain (Social Science Review, 2023)
Following the recent 2017 Rohingya influx, Bangladesh now hosts nearly one million Rohingyas. Being persecuted by the Myanmar state machinery and some local vigilantes, they fled for safe refuge in Bangladesh’s Cox's Bazar. Bangladesh sheltered them in 34 overcrowded camps located in the Teknaf and Ukhiya sub-districts of Cox’s Bazar. At present, Rohingyas are counted more than double compared to the local host population in these two areas. This study makes efforts to explicate why and how these stranded Rohingyas can be a security threat to Bangladesh. Theoretically, the study relies on security discourse; ecological and resource scarcity model; and relative deprivation theory. Under the qualitative research approach, the researchers conducted semi-structured interviews mainly with key informants and subject experts to gather field data. The study brings out that this overpopulation has perplexed the security milieu of the country and forecasts multifaceted internal security threats. Thus, the study offers salient policy recommendations to ameliorate the crisis response by neutralizing the identified and forecasted conflictual issues. Social Science Review, Vol. 40(1), Jun 2023 Page 89-107